Analysis of the Influence of Tensioned Intervening Pipe on the Overall Performance of Deepwater Self-elevating Wellhead Platform - Wang, Yuehong (Scientific Journal of Technology, 2026)
For deepwater jack-up wellhead platforms, a tensioner-based design scheme for tensioning the riser pipe is proposed. Based on the displacement and stress response of the riser pipe, three riser pipe sizes and corresponding tension forces were selected. Furthermore, a coupled analysis model was established between the tensioned riser pipe and the jack-up platform. Under a 550-ton tension force, the impact of three riser pipe models on the overall performance of the deepwater mobile wellhead platform was analyzed. The results indicate that the tensioned riser pipe can reduce the first two natural frequencies of the platform and mitigate the dynamic amplification effect of wave loads. As the riser pipe diameter increases, the proportion of wave loads on the riser pipe body relative to the total platform load rises, along with the load transmitted to the platform hull. While providing stiffness to the platform, the tensioned riser pipe adversely affects horizontal displacement and leg strength, with the impact becoming more pronounced as the riser pipe diameter increases. In summary, the 914×40mm tensioned riser pipe design demonstrates potential feasibility, but further optimization is required for riser strength at the mud surface, overall platform stiffness, and leg chord strength.